2015
DOI: 10.3109/03630269.2015.1107842
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of anAγ-Globin Gene Promoter Variant (HBG1: g.-225_-222delAGCA) Underlines Its Role in Increasing Fetal Hemoglobin Levels Under Erythropoietic Stress

Abstract: Hereditary persistence of fetal hemoglobin (HPFH) is a condition characterized by persistent γ-globin gene expression and synthesis of high levels of fetal hemoglobin (Hb F; α2γ2) during adult life. It is usually caused by promoter variants or large deletions affecting the human fetal globin (HBG1 and HBG2) genes. Some of these HPFH-causing variants, such as HBG2: g.-158 C > T, exert their effect only under conditions of erythropoietic stress, typical for β-thalassemia (β-thal) patients. Namely, the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The HBG1 and HBG2 are normally expressed in the fetal liver, spleen and bone marrow. Compared with wild type promoter, the activity of HBG1 gene promoter variant decreased significantly in K562 cells under conditions of erythropoietic stress [ 34 ]. This finding is helpful to analyze the pathogenesis of β-Thalassemia and provide a reference for its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The HBG1 and HBG2 are normally expressed in the fetal liver, spleen and bone marrow. Compared with wild type promoter, the activity of HBG1 gene promoter variant decreased significantly in K562 cells under conditions of erythropoietic stress [ 34 ]. This finding is helpful to analyze the pathogenesis of β-Thalassemia and provide a reference for its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These included the -AGCA deletion at −225 to −222 of A γ -globin gene promoter, rs5006884 (C>T) on OR51B6 gene, −158 G γ - Xmn I, BCL11A binding motifs between A γ - and δ -globin genes as well as the whole γ -globin gene sequencing. It has been shown that the four bp deletion (-AGCA) at −225 to −222 of the A γ -globin gene was associated with reduced A γ -globin chain and elevation of G γ chain with slightly increased Hb F level in β -thalassemia subjects ( Manca et al, 1991 ; Ugrin et al, 2016 ). The rs5006884 (C>T) on OR51B6 gene located upstream of β -globin gene cluster might intervene in the tetramer formation of α -globin chain with β - and δ -globin chains and regulated Hb A 2 level in β -thalassemia carriers ( Cyrus et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%